Are calendar anomalies still alive and not just illusions? : a 36-years perspective in Singapore stock market. - Ong, Min Guan. (2010)
This study investigates the effects of day-of-the-week, turn-of-the-month, turn-of-the-year and holiday (cultural and non-cultural) on Singapore stock returns between 1973 and 2008. Drawing parallel to previous research that focuses on Christmas effect on stock returns in European and USA markets, we find interesting results on Chinese New Year effect on Singapore stock returns. Cultural holiday aside, we also discover significant post-New Year effect. Surprisingly, post-New Year effect reverses during the period 2003-2007. Using post-New Year effect, we devise a possible trading strategy, taking into account the necessary transaction costs. This paper also reports findings similar to prior research: Monday’s and Tuesday’s returns are lower than that of Wednesday’s to Friday’s; positive returns are found during turn-of-month and post holidays. In general, however, the effects have declined over the years. The results are not surprising given the growing sophistication of stock market. Also, in contrast to numerous research conducted in the USA context, we find no significant turn-of-year effect in Singapore stock market.